STUDI NUMERIK TERHADAP DAKTILITAS PERPINDAHAN STRUKTUR BAJA PORTAL TERBUKA SEDERHANA - Haris HG. (NIM 25099105), Sabril
Abstract : This thesis presents the results of numerical study on displacement ductility of simple moment-resisting frame steel structure. Observation on element stress-strain and deformation using non-linear finite element MSC/NASTRAN shows that the lateral-torsional stability of the frame and inelastic deformation capacity at the flanges area have to be satisfied to ensure the good structural ductility. By observing ultimate states on series of structures, parametric study was carried out to assess the influences of some parameters on the value of displacement ductility of structure. The most significant parameter is the height-width of section ratio (h/b) and followed by steel grade (fy), height-width of frame ratio (WL), width-thickness of flange ratio (b/2tf), column slenderness (H/ry), and inertia of column-beam ratio (Ic/Ib). All parameters are normalized and formulated in a new parameter, RATIO, by giving the coefficient of order for each parameter according to its influence to the ductility value. A formula is proposed to estimate displacement ductility value as a function of RATIO. Some experimental results used to verify this formula show a good agreement.